Dig [videorecording (DVD)] - Ablakhad, Banipal; Ablakhad, Benhur; Jane, Thomas; Liberato, Liana, 1995-; Hirsch, Emile, 1985- (Saban Films, 2022)
Scott Brennan is trying to piece together a life shattered by a road rage incident that killed his wife and left his teen daughter Jane deaf and resentful of him. Still hoping to mend things with Jane a year later, Brennan accepts a contract for a high-paying demolition job in the desolate New Mexico sprawl outside Las Cruces. When he and Jane arrive at the site, they are suddenly taken hostage by a dangerous couple, who will stop at nothing to retrieve what lies beneath the property. Now, father and daughter must work together to outsmart their captors and survive the grueling night.